Influence of two collection frequency intervals on sperm quality of standard and miniature bull Terriers during short breeding periods: A clinical field study - J. Salvado; D. Catilina; P. Borges; J. Simoes; A. Martins-Bessa (Veterinary World, 2024)
Background and Aim: The quality of canine sperm can be influenced by many factors, such as breed, body weight, age, ejaculatory frequency, nutrition, and environment. In the UK, it is common practice for standard Bull Terriers (SBT) and miniature Bull Terriers (MBT) to require male donors during a short breeding period. The aim of this study was to evaluate the effect of semen collection frequency on ejaculate volume and nine sperm parameters in SBT and MBT males, considering age and body condition score (BCS).